The role of bio-inspired hierarchical structures in wetting - Grewal, H. S.; Cho, Il-Joo; Yoon, Eui-Sung (IOP PUBLISHING LTD, 2015)
Superhydrophobicity facilitates the development of self-cleaning, anti-biofouling, and anti-corrosion surfaces. The leaves of the lotus (Nelumbo nucifera) and taro (Colocasia esculenta) plants are well known for their self-cleaning properties. A hierarchical structure comprising papillae epidermal cells superimposed with epicuticular wax crystalloids of varying shapes, sizes, and orientations is an important aspect of the surface of these plant leaves. We fabricated two types of hierarchical structures biomimicking the surface topography of the lotus leaf. The hierarchical patterns successfully demonstrated the superhydrophobic state in comparison with nano and micro patterns. We used the finite element method (FEM) to simulate and understand the wetting process. The FEM simulations showed good correlation with the experimental results. FEM was helpful in understanding the wetting of enormously complex biological surfaces with relative ease, and it qualifies as a potential tool for designing superhydrophobic surfaces. Using the FEM frame work, we further designed surfaces to optimize the order of the shapes in hierarchy. The results showed that the superhydrophobic surface with the lowest wetted area was obtained by placing shapes with smaller geometric angles at the top of the hierarchy. This arrangement of shapes provides the optimum combination of superhydrophobicity and surface integrity. This observation explains why the hierarchical structure of many superhydrophobic leaves follows this order. We also investigated the complex hierarchical structure of Salvinia minima. Owing to its remarkable ability to entrap air and pin the contact line, it exhibits superhydrophobicity along with the much-required Cassie state. These properties of Salvinia minima make it an excellent candidate for developing omniphobic surfaces.
Keywords: SURFACES; LOTUS; NANOSTRUCTURES; RESISTANCE; ROUGHNESS; STATES